Design, politics and subjectivization - Carvalho, Ricardo Artur Pereira; Necyk, Barbara; Martins, Bianca; Altmayer, Guilherme (DAT Journal, 2024)
The article presents the line of research Design, Politics and Subjectivation, linked to the Graduate Program in Design at Rio de Janeiro State University (PPDESDI/ UERJ). Firstly, the context and formation process of this line of research is presented. Next, the foundations that characterize and guide the line are presented. Finally, the research strands of the line are presented, namely: Design in educational practices; Design, body and technopolitics; Design, technicities and sensitivities; Design and oppression.